2015
DOI: 10.1105/tpc.15.00562
|View full text |Cite
|
Sign up to set email alerts
|

SMAX1-LIKE/D53 Family Members Enable Distinct MAX2-Dependent Responses to Strigolactones and Karrikins in Arabidopsis

Abstract: The plant hormones strigolactones and smoke-derived karrikins are butenolide signals that control distinct aspects of plant development. Perception of both molecules in Arabidopsis thaliana requires the F-box protein MORE AXILLARY GROWTH2 (MAX2). Recent studies suggest that the homologous SUPPRESSOR OF MAX2 1 (SMAX1) in Arabidopsis and DWARF53 (D53) in rice (Oryza sativa) are downstream targets of MAX2. Through an extensive analysis of loss-of-function mutants, we demonstrate that the Arabidopsis SMAX1-LIKE ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
521
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 356 publications
(564 citation statements)
references
References 79 publications
20
521
0
1
Order By: Relevance
“…Thus, as is the case in many other hormonal signaling pathways in plants, the regulated degradation of target proteins by the 26S proteasome appears to be a key feature of SL signaling. The principle proteolytic targets of SL signaling appear to be a clade of proteins in the SMAX1-LIKE (SMXL) family, typified by SMXL7 in Arabidopsis thaliana and D53 in rice (Oryza sativa) (Jiang et al, 2013;Zhou et al, 2013;Soundappan et al, 2015;Wang et al, 2015). SMXL proteins are weakly homologous to HEAT SHOCK PROTEIN101 ClpB chaperonins and are named for the founding member, SUPPRESSOR OF MAX2 1 (SMAX1) (Stanga et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, as is the case in many other hormonal signaling pathways in plants, the regulated degradation of target proteins by the 26S proteasome appears to be a key feature of SL signaling. The principle proteolytic targets of SL signaling appear to be a clade of proteins in the SMAX1-LIKE (SMXL) family, typified by SMXL7 in Arabidopsis thaliana and D53 in rice (Oryza sativa) (Jiang et al, 2013;Zhou et al, 2013;Soundappan et al, 2015;Wang et al, 2015). SMXL proteins are weakly homologous to HEAT SHOCK PROTEIN101 ClpB chaperonins and are named for the founding member, SUPPRESSOR OF MAX2 1 (SMAX1) (Stanga et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of the best-characterized of these interactions is between the EAR motif in Aux/IAA proteins (repressors of auxin signaling) and the TOPLESS RELATED (TPR) family of chromatin remodeling factors (Szemenyei et al, 2008). The EAR motif in SMXL7 permits relatively weak interaction with TPR proteins, particularly TPR2 (Soundappan et al, 2015;Wang et al, 2015). On this basis, it has been suggested that SMXL proteins act as regulators of transcription (Smith and Li, 2014), but the functional relevance of this interaction, and indeed the EAR motif in general, has not been established.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations